Complex transradial carpal dislocation in a Professional Pianist: Case Report - Pedrazzini, Alessio; Paterlini, Marco; Pompili, Massimo; Tocco, Silvio; Ceccarelli, Francesco (Acta Biomedica Atenei Parmensis, 2014)
Carpal fracture-dislocation associated to distal radius fractures is an uncommon injury of the wrist. Clinical assessment, instrumental diagnosis and treatment are all challenges for the surgeon. In addition, the prognosis in high-functioning patients is nearly always poor. The authors describe an early diagnosis of scapholunate dissociation and joint capsule tear associated with radial styloid and triquetral fractures in a 39-year-old professional piano player. A dorsal approach was used to reduce and fixate the fracture with k-wires, and to repair soft-tissue injuries with a Titanium micro-anchor. Early controlled mobilization was prescribed post-operatively. No other similar investigations were found because of the various associated fractures in the current case study, which normally excludes subjects from retrospective outcome studies on wrist ligament repair. Early diagnosis and surgical management associated with early controlled mobilization resulted in excellent clinical outcomes, according to radiograph imaging, the Italian version of the DASH score (Disabilities of the Arm, Shoulder and Hand), goniometry and dynamometry.